IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NO. 46 TAHUN 2010 TERHADAP HAK DAN KEWAJIBAN KEPERDATAAN ANAK HASIL PERNIKAHAN SIRI DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Ilahi, Ahmad Farhan; Aspandi, Aspandi; Sayehu, Sayehu (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Constitutional Court Decision Number 46 of 2010 accommodates the civil rights and obligations of children of sirri marriages. This decision has implications for civil rights and obligations that are not stipulated by Law Number 16 of 2019 amendments to Law Number 1 of 1974 concerning Marriage. This study aims to analyze the implications of the results of the decision of the Constitutional Court Number 46 of 2010 on the civil rights of children of unregistered marriages with their biological fathers. This study also aims to analyze the implications of the results of the Constitutional Court decision No. 46 of 2010 on the rights and obligations of children of unregistered marriages regarding the provisions of Law No. 16 of 2019 amendments to Law No. 1 of 1974 concerning Marriage. This research is a type of qualitative research that reveals the implications of civil law and rights and obligations for children of sirri marriages. This research is also library research, examining the implications of the decision of the Constitutional Court Number 46 of 2010 on the civil rights and obligations of children of siri marriages that are not stipulated by Law Number 16 of 2019 amendment to Law Number 1 of 1974 concerning Marriage. The primary source of research data is the document resulting from the decision of the Constitutional Court Number 46 of 2010 concerning children of sirri marriages. This research is also supported by secondary sources in the form of documents resulting from other decisions, as well as related research results. This research data collection method through documentation of primary sources and secondary sources. This study uses a normative juridical approach by explaining the implications of civil rights and obligations for children of sirri marriages with the perspective of the results of the Constitutional Court’s decision. The results of the study show that the decision of the Constitutional Court Number 46 of 2010 has implications for the civil rights of children of siri marriages with their biological fathers but must be based on reliable evidence. Decision of the Constitutional Court Number 46 of 2010 has implications for the rights and obligations for children of a siri marriage with legitimate children as regulated in articles 45 to 49 of Law Number 16 of 2019 amendments to Law Number 1 of 1974 concerning Marriage. Keywords: Constitutional Court, Civil Rights and Obligations, Sirri Marriage Abstrak: Putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 mengokomodir hak dan kewajiban keperdataan anak hasil pernikahan sirri. Putusan tersebut berimplikasi terhahap hak dan kewajiban keperdataan yang tidak ditetapkan oleh Undangundang Nomor 16 Tahun 2019 perubahan atas Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan.Penelitian ini bertujuan menganalisis implikasi hasil putusanMahkamah Konstitusi Nomor 46 Tahun 2010 terhadap hak keperdataan anak hasil pernikahan siri dengan ayah biologisnya. Penelitian ini juga bertujuan menganalisis implikasi hasil putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 terhadap hak dan kewajiban bagi anak hasil pernikahan siri terhadap ketentuan Undang-undang Nomor 16 Tahun 2019 perubahan atas Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan.Penelitian ini merupakan jenis penelitian kualitatif yang mengungkap implikasi hukum keperdataan serta hak dan kewajiban bagi anak hasil pernikahan sirri. Penelitian ini juga merupakan penelitian Pustaka, mengkaji implikasi hasil putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 terhadap hak dan kewajiban keperdataan anak hasil pernikahan siri yang tidak ditetapkan oleh Undang-undang Nomor 16 Tahun 2019 perubahan atas Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan. Sumber primer data penelitian ini yaitu dokumen hasil putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 tentang anak hasil pernikahan sirri.Penelitian ini juga didukung sumber sekunder berupa dokumen-dokumen hasil putusan lainnya, serta hasil penelitian yang terkait.Metode pengumpulan data penelitian ini melalui dokumentasi sumber-sumber primer dan sumber-sumber sekunder.Penelitian ini menggunakan pendekatan yuridis normatif dengan menjelaskan implikasi hak dan kewajiban keperdataan bagi anak hasil pernikahan sirri dengan perspektif hasil putusan Mahkamah Konstitusi.Hasil penelitian menunjukkan bahwa putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 berimplikasi pada hak keperdataan anak hasil pernikahan siri dengan ayah biologisnya namun harus didasari dengan pembuktian yang dapat dipertanggungjawabkan. Putusan Mahkamah Konstitusi Nomor 46 Tahun 2010 berimplikasi pada hak dan kewajiban bagi anak hasil pernikahan siri sama dengan anak sah yang diatur dalam pasal 45 sampai dengan pasal 49 Undang-undang Nomor 16 Tahun 2019 perubahan atas Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan. Kata kunci: Mahkamah Konstitusi, Hak dan Kewajiban Keperdataan, Pernikahan Sirr